2016
DOI: 10.1109/tie.2016.2569067
|View full text |Cite
|
Sign up to set email alerts
|

Sound Quality Evaluation of Noise of Hub Permanent-Magnet Synchronous Motors for Electric Vehicles

Abstract: The existing evaluation methods and indexes of noise of electric motors can not comprehensively reflect all the physical characteristics of noise of hub permanent magnet synchronous motors (HPMSM) and human subjective sensations. In this paper, a method of the sound quality (SQ) evaluation of HPMSM for electric vehicles is proposed. The method is divided into three steps. In the first step, a noise objective evaluation of HPMSM with seven acoustical objective indexes, including loudness, roughness, A-weighted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 12 publications
0
24
0
Order By: Relevance
“…The external rotor PMBLDCM studied in this paper is surface mounted, the permanent magnet field in polar coordinates is calculated by the equivalent remanence method and complex relative air-gap permeance, the radial magnetic flux density of permanent magnet considering the slotting effect B rm r, α, t can be expressed as [3,24,25]…”
Section: Analytical Calculation Of No-load Radial Magnetic Field Withmentioning
confidence: 99%
“…The external rotor PMBLDCM studied in this paper is surface mounted, the permanent magnet field in polar coordinates is calculated by the equivalent remanence method and complex relative air-gap permeance, the radial magnetic flux density of permanent magnet considering the slotting effect B rm r, α, t can be expressed as [3,24,25]…”
Section: Analytical Calculation Of No-load Radial Magnetic Field Withmentioning
confidence: 99%
“…Sharpness reflects the frequency characteristics of the sound. 17 The higher the proportion of high-frequency sound, the higher the sound sharpness will be. Sharpness also reveals the harsh degree of the sound signal.…”
Section: Sharpness Of Wind Buffeting Noisementioning
confidence: 99%
“…Meanwhile, it is possible to design an SQ estimation model by utilizing an ANN to simulate the subjective assessment model in an approximation process of the subjective perception. Many researchers have applied ANNs to SQ evaluation, and they have achieved reliable results [15][16][17][18][19][20]. Steinbach and Altinsoy [15] used ANNs to predict the annoyance evaluations of the pass-by noise of EVs and found that most of the parameters have no linear influence on the annoyance perception.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [19] proposed a method for predicting the SQ of vehicle interior noise using a BP-ANN that is based on particle swarm optimization (PSO). In addition, Ma et al [20] established an SQ evaluation model of hub-driven motors based on a BP-ANN, and they also proposed the limitations of the BP-ANN model. In order to improve the prediction accuracy, the structural parameters of BP-ANNs need to be optimized, but this process consumes a lot of time.…”
Section: Introductionmentioning
confidence: 99%